Neurofibromatosis type 1 – association with breast cancer, basal cell carcinoma of the skin, and low-grade peripheral nerve sheath sarcoma: case report and literature review (2019)
Neurofibromatosis type 1 is a rare medical condition that raises the probability of having distinct types of malignant and benign neoplasms. Nevertheless, the association with breast cancer is rare, and metachronic neoplasia with a distinct histologic subtype is an association that has never been reported before. Here we describe a case of a primary breast tumor, with posterior development of basal cell carcinoma of the skin, and a low-grade peripheral nerve sheath sarcoma.